A lightweight AES algorithm implementation for encrypting voice messages using field programmable gate arrays - Kumar, Keshav; Ramkumar, K.R.; Kaur, Amanpreet (Journal of King Saud University. Computer and information sciences, 2022)
The security of data is a major concern in this digital era. In general text and image data are well protected with the help of existing standards, meanwhile, securing voice communications is a challenging task. In the literature, there are some methods found using oscillators and chaotic signals for protecting direct voice communications, but they have limited functionalities due to synchronization problems between chaotic signals and oscillators. This paper gives an idea of encrypting voice signals over peer to peer communication with the help of a modified and lightweight AES algorithm. This algorithm is similar to the traditional AES algorithm in most of the aspects but does not imply the use of mix column that is used in the traditional AES algorithm. The lightweight algorithm is tested on two different Field Programmable Gate Array (FPGA) and the designs are analyzed with respect to time delay and effective utilization of resources.